A THE INFLUENCE OF THE COST OF ELECTRICITY PRODUCTION ON THE FORMATION OF TARIFFS : THE INFLUENCE OF THE COST OF ELECTRICITY PRODUCTION ON THE FORMATION OF TARIFFS - To‘xtashev, Alisher; Kadirov, Kamoliddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article examines the impact of renewable energy sources, specifically solar photovoltaic (PV) systems and hydropower, on load indicators and the cost of electricity production (tannarx) in Uzbekistan's industrial power grids. The study compares traditional thermal power plants (gas and coal) with renewable sources, analyzing their production costs. The article calculates the approximate tannarx for gas (305–596 UZS/kWh), coal (848.4 UZS/kWh), solar PV (253–483 UZS/kWh), and hydropower (300–400 UZS/kWh). Additionally, the challenges of integrating solar PV systems into the grid, including issues related to daily and seasonal production stability, are explored, and energy storage solutions are considered. The results indicate that increasing the use of renewable sources can minimize the current costs associated with gas and coal power plants by improving performance indicators.